Dosimetric verification of monaco treatment planning system (TPS) in heterogeneous medium for 6 mv linac - Azlan, Adriana Batrisyia Noor Mohd (2024)
The Monaco TPS, employing the Monte Carlo dose calculation algorithm, offers high precision in radiotherapy planning. Accurate dose calculation in heterogeneous tissues necessitates comprehensive commissioning and verification due to its impact on patient outcomes. This study evaluates the dose calculation accuracy of Monaco TPS using Rando phantoms, thermoluminescence dosimeters (TLD-100) dosimeters, EBT3 Gafchromic films, and clinical patient data through patient-specific quality assurance (PSQA). Methods : Dosimetric verification of Monaco TPS was conducted on a head and neck Rando phantom for 3D conformal radiotherapy (3DCRT) whole brain radiotherapy (WBRT) and volumetric modulated arc therapy (VMAT) meningioma planning in heterogeneous environments, using 12 TLD-100s and EBT3 Gafchromic films. Additionally, six Eclipse TPS patient plans were replicated on Monaco TPS, and PSQA was performed using gamma criteria of 3% dose difference (DD) and 3 mm distance-to-agreement (DTA). Results :Monaco TPS demonstrated consistent percentage deviations within ±10% (ranging from 1.8% to 9.1%) between TPS calculated and TLD-measured doses for 3DCRT, with no significant difference (p > 0.05). EBT3 Gafchromic film dosimetry showed good agreement with TPS dose distributions, achieving a 97.3% gamma passing rate. However, VMAT planning revealed significant deviations (3.06% to 67.88%) between calculated and measured doses, with a significant difference (p < 0.01) and a 52.5% gamma passing rate for film dosimetry. PSQA for six patient plans yielded high gamma passing rates (97.5% to 100%) and absolute dose deviations ranging from 0.29% to 3.48%.Conclusion : Monaco TPS is reliable and accurately commissioned for 3DCRT planning but shows significant deviations in VMAT planning. Future efforts should aim to improve verification methods, address challenges in gamma index analysis, and enhance VMAT dose calculation accuracy for consistent treatment planning.